2019
DOI: 10.30831/akukeg.469277
|View full text |Cite
|
Sign up to set email alerts
|

Okul Bazlı Bütçeleme (OBB) Uygulamasının Okul Geliştirme İşlevi Açısından Değerlendirilmesi

Abstract: It was aimed to determine the opinions of school administrators on the implementation of School-Based Budgeting (SBB) and the contributions of SBB to school development in this study. The qualitative methods were used in this descriptive study. The study group consisted of 29 primary and secondary school administrators. After data of the study were obtained through semi structured interviews and focus group interviews. School administrators' opinions on authority and responsibilities of school management withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…The participants recommend transitioning to a school-based budgeting system and making legal arrangements to strengthen the positions of school managers in finding and using resources. There are studies that find similar suggestions in the literature (Balkar, Küçükbere and Akşab, 2019;Yamaç, 2010).…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…The participants recommend transitioning to a school-based budgeting system and making legal arrangements to strengthen the positions of school managers in finding and using resources. There are studies that find similar suggestions in the literature (Balkar, Küçükbere and Akşab, 2019;Yamaç, 2010).…”
Section: Resultssupporting
confidence: 61%
“…In another study, it was determined that thirty different sources of financing were utilized to meet these needs and it was suggested that the resources should be strengthened by increasing the resources in order to meet the expenses of the schools and that basic education schools, like secondary schools, should make their own expenses by taking direct budget from the Ministry (Yamaç, 2010). Balkar, Küçükbere and Akşab (2019) investigated how School Based Budgeting (SBB) would contribute to school development. Within the scope of the research, the views and suggestions of the school principals on the use of the fund tracking module, the establishment of a school-based budget and the effects of the SBB on school development were examined.…”
Section: Theoretical Frameworkmentioning
confidence: 99%